Rethinking Communication in Interactions with a Child with Autism: Ela, Her Father, and the Jellyfish in the Pool - Nora Lucía Gómez-Victoria; Katerine Carvajal; Sebastián Collazos; Yerly Muñoz; Angie Quinchia (Scandinavian Journal of Disability Research)
We share the results of qualitative research with a case study methodological design to contribute to the emerging narratives claiming the unique languaging practices developed in the experiences of people with nonverbal autism. Taking a relational ontology stance, we use the concept of languaging as a continuous coordination of actions alongside the notion of assemblages of semiotic repertoires configured within multimodal and multisensory ecologies to analyze the communication between a child, Ela and her father, Gus, during a social activity at the pool. A multilevel-multimodal transcription was made to characterize the communication; the video recordings were complemented by the thematic analysis of the parents’ accounts and opinions. The analysis led us to the conclusion that, through this approach, communication can be understood as a unique and solidary encounter. This highlights that we already possess both the conceptual and methodological resources necessary to appreciate communication in all its diverse forms.